Human Resources Distribution Among Tehran University Of Medical Sciences Hospitals - Seyed Javad Ghazi Mirsaeid; Mahya Mirzaie; Elham Haghshenas; Hossein Dargahi (Tehran University of Medical Sciences, 2014)
Background and Aim: Today, healthcare system is exposed to inappropriate human resources distribution challenges in all over the world. So far there is not an appropriate policy for human resources distribution in Iran. This deficiency may cause several problems for providing healthcare services. This research was aimed to determine the situation of human resources distribution among Tehran University Of Medical Sciences (TUMS) Hospitals. Materials and Methods: This is a cross-sectional definitive study induced in four general and special TUMS hospitals. The research tool was a checklist that determine the number of nurses, paraclinic and supportive employees and finally the decrease and increased of the human resources among the departments of the hospitals regarding Iranian Ministry of Health (MOH) issues. The data was collected and analyzed by SPSS software and determined the differences between current situation in accordance to MOH issues. Results: We observed the deficiency of human resources among all studied hospitals. Also the distribution of human resources among most of the hospitals departments was not coordinated with MOH issues. Conclusion : It seems the distribution of human resources among Iranian healthcare system is not followed by a special model. Therefore, we suggest the model of health human resources planning should be determined and related by information, providers, services, education and policy as healthcare system factors and overlapping of these factors.